2017
DOI: 10.3803/enm.2017.32.2.200
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Guidelines for the Management of Adrenal Incidentaloma

Abstract: An adrenal incidentaloma is an adrenal mass found in an imaging study performed for other reasons unrelated to adrenal disease and often accompanied by obesity, diabetes, or hypertension. The prevalence and incidence of adrenal incidentaloma increase with age and are also expected to rise due to the rapid development of imaging technology and frequent imaging studies. The Korean Endocrine Society is promoting an appropriate practice guideline to meet the rising incidence of adrenal incidentaloma, in cooperatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
109
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(119 citation statements)
references
References 118 publications
(188 reference statements)
4
109
0
6
Order By: Relevance
“…Under these circumstances, some consensual diagnostic and therapeutic guidelines have been established. A consensus meeting for AIs was held at the National Institutes of Health in 2002 [10], and the guidelines of the European Society of Endocrinology (ESE) collaborated with the European Network for the Study of Adrenal Tumors (ENSAT) [3], the American Association of Clinical Endocrinologists (AACE) collaborated with the American Association of Endocrine Surgeons (AAES) [12], Korean Endocrine Society [13], and some reviews discussing this issue have been reported [14], and it has been becoming clear how to manage AIs. We therefore performed a nationwide multicenter study as a project of the Research Committee on Disorders of Adrenal Hormones, proposed on behalf of the Japanese Ministry of Health, Labour and Welfare, from 1999 to 2004.…”
mentioning
confidence: 99%
“…Under these circumstances, some consensual diagnostic and therapeutic guidelines have been established. A consensus meeting for AIs was held at the National Institutes of Health in 2002 [10], and the guidelines of the European Society of Endocrinology (ESE) collaborated with the European Network for the Study of Adrenal Tumors (ENSAT) [3], the American Association of Clinical Endocrinologists (AACE) collaborated with the American Association of Endocrine Surgeons (AAES) [12], Korean Endocrine Society [13], and some reviews discussing this issue have been reported [14], and it has been becoming clear how to manage AIs. We therefore performed a nationwide multicenter study as a project of the Research Committee on Disorders of Adrenal Hormones, proposed on behalf of the Japanese Ministry of Health, Labour and Welfare, from 1999 to 2004.…”
mentioning
confidence: 99%
“…КТ без контрастного підсилення (нативна фаза)обов'язковий етап діагностичного пошуку при патології як ПЩЗ, так і НЗ. Залежно від розмірів, структурних особливостей та щільності утворення НЗ у нативній фазі сканування лікар-радіолог приймає рішення щодо проведення дослідження з контрастним підсиленням [14,15].…”
Section: обґрунтування комбінованого дослідження прищитоподібних та нunclassified
“…Pheochromocytomas are rare, mostly benign tumours arising from chromaffin cells of the adrenal medulla or many extra-adrenal locations (where they are called paragangliomas). They constitute 7% (1.5-14%) of all adrenal incidentalomas [1] and are extremely rare in pregnant women, with a prevalence of 1 in 54,000 pregnancies [2]. The diagnosis is a demanding challenge because the clinical picture ranges from asymptomatic cases to life-threatening hypertensive crises.…”
Section: Introductionmentioning
confidence: 99%